Long-term trends of HIV/AIDS incidence in India: an application of joinpoint and age–period–cohort analyses: a gendered perspective - Shri, Neha; Bhattacharyya, Krittika; Dhamnetiya, Deepak; Singh, Mayank; Jha, Ravi Prakash; Patel, Priyanka (Frontiers in Public Health, 2023)
Background: Monitoring the transmission patterns of Human Immunodeficiency Virus (HIV) in a population is fundamental for identifying the key population and designing prevention interventions. In the present study, we aimed to estimate the gender disparities in HIV incidence and the age, period, and cohort effects on the incidence of HIV in India for identifying the predictors that might have led to changes in the last three decades. Data & Methods: This study utilizes data from the Global Burden of Disease Study for the period 1990-2019. The join point regression analysis was employed to identify the magnitude of the changes in Age Standardized Incidence Rates (ASIRs) of HIV. The average annual percentage changes in the incidence were computed and the age-period-cohort analysis was performed. Results: A decreasing trend in the overall estimates of age-standardized HIV incidence rates were observed in the period 1990-2019. The joinpoint regression analysis showed that the age-standardized incidence significantly declined from its peak in 1997 to 2019 (38.0 & 27.6 among males and females per 100,000 in 1997 to 5.4 and 4.6 respectively in 2019). The APC was estimated to be 2.12 among males and 1.24 among females for the period 1990-2019. In recent years, although the gender gap in HIV incidence has reduced, females were observed to bear a proportionately higher burden of HIV incidence. Age effect showed a decline in HIV incidence by 91.1% and 70.1% among males and females in age 15-19 years to 75-79 years. During the entire period from 1990-94 to 2015-19, the RR of HIV incidence decreased by 36.2% and 33.7% among males and females respectively. Conclusion: India is experiencing a decline in new HIV infections in recent years. However, the decline is steeper for males than for females. Findings highlight the necessity of providing older women and young women at risk with effective HIV prevention. This study emphasizes the need for large-scale HIV primary prevention efforts for teenage girls and young women.